Voltammetry at porous electrodes: A theoretical study - Barnes, E; Chena, X; Li, P; Compton, R (Elsevier, 2014)
Theory is presented to simulate both chronoamperometry and cyclic voltammetry at porous electrodes fabricated by means of electro-deposition around spherical templates. A theoretical method to extract heterogeneous rate constants for quasireversible and irreversible systems is proposed by the approximation of decoupling of the diffusion within the porous electrode and of bulk diffusion to the electrode surface.